BURUNG ELANG DALAM KARYA SENI LUKIS KONTEMPORER - Alga Surista Pura, Drs. Erfahmi, M.Sn., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of this article is to visualize the unique behavior of eagle's life as a guide and motivation in human life through contemporary painting. Eagle as an ideas in this article as a medium of information to the public to be able to admire eagles so eager to maintain their habitat. This method in realizing ideas of art include: preparation, elaboration stage, synthesis, concept realization and completion. This work describes the behavior of eagles in the wild. As a result of the discussion and stages creation of ten (10) works that gives more motivation, information, as well as learning to make human character in life and theirs life.Kata kunci: Burung Elang, Seni Lukis Kontemporer